Study Kelayakan Bisnis dan Kewirausahaan pada UMKM Balikpapan - Pinem, Anwar Arifin; Rahmayuni, Siti; Ramadhani, Naya Thalita (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Business and entrepreneurship feasibility studies are important aspects in the development of Micro, Small, and Medium Enterprises (MSMEs) in Balikpapan, which function to understand the potential and risks of business in the area. Objective: The purpose of this service is to assist MSMEs in Balikpapan in analyzing business feasibility and improving entrepreneurship through appropriate education and training. Method: This service method involves interactive training and mentoring for MSME actors, including market analysis, business plan preparation, and production cost calculations. Result: The results of this activity show an increase in MSME understanding of business feasibility studies, better access to financing sources, and closer collaboration with local governments. Conclusion: This service program has succeeded in providing a positive impact on the growth and competitiveness of MSMEs, and can be used as a model for developing entrepreneurship in other areas.